Association between frailty index and mortality in depressed patients: results from NHANES 2005–2018 - Xiaoqiang Liu; Yubin Wang; Yingxuan Huang; Chanchan Lin; Boming Xu; Yilin Zeng; Peizhong Chen; Xiaobo Liu; Yisen Huang (Scientific Reports)
Abstract This study investigated the relationship between the frailty index and all-cause and cause-specific mortality in patients with depression. We recruited 2,669 participants with depression from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018 and quantified their frailty status using a 53-item frailty index. Cox proportional hazards models were used to estimate hazard ratios (HR) and their 95% confidence intervals (CI). The median (IQR) frailty score was 0.3 (0.2, 0.4). During a median follow-up of 7.1 years, 342 all-cause deaths (including 85 cardiovascular deaths and 70 cancer deaths) were recorded. Compared to the lowest frailty index tertile, the adjusted HR (95% CI) for all-cause mortality in the highest tertile was 2.91 (1.97, 4.3), for cardiovascular mortality was 3.13 (1.37, 7.19), and for cancer mortality was 2.3 (1.05, 5.03). Each unit increase in the frailty index (log-transformed) was associated with a 241% increase in all-cause mortality (P < 0.001), a 233% increase in cardiovascular mortality (P < 0.001), and a 185% increase in cancer mortality (P < 0.001). These results were consistent across analyses stratified by age, gender, race, BMI, hypertension, and diabetes. This study suggests that the frailty index is positively associated with all-cause and cause-specific mortality in patients with depression. The frailty index could serve as a prognostic indicator, and frailty interventions should be an important part of managing patients with depression.